Warming outweighs nitrogen deposition in shaping rhizosphere microbial structure involved in carbon, nitrogen, and phosphorus cycling in Ambrosia trifida - Xu, Ke; Guan, Ping; Du, Wanyu; Zeng, Huiyu; Chen, Meishan; Lv, Zhenhuan; Liu, Yanhan; Shao, Meini; Qu, Bo (Frontiers in Plant Science, 2026)
IntroductionAmbrosia trifida, a harmful invasive plant, poses significant ecological and economic threats and is expected to spread further under future warming and nitrogen deposition scenarios. According to plant-soil feedback and enhanced mutualist hypothesis, invasive plants may gain a competitive edge by recruiting specific microorganisms. However, little is known about the composition and functional potential of its rhizosphere microbiome.MethodsIn this study, we combined metagenomics with widely targeted metabolomics to investigate the interactions between root exudates and soil microbial communities under experimental warming and nitrogen deposition.Results and discussionThe results showed that warming and nitrogen addition together promoted biomass accumulation. And their combination enhanced soil nutrient content. Warming increased the abundance of functional genes involved in carbon fixation (e.g., acs, acsA, PCCA, MUT), whereas nitrogen addition suppressed nitrification and denitrification genes. Warming also enhanced the abundance of genes related to inorganic phosphate solubilization (ppk, ppx), phosphorus mineralization (phnPP, phnF, glpQ), and phosphorus transport (pstBC, ugpABCE). Functionally, warming increased the relative abundance of beneficial taxa such as Sphingomicrobium, Massilia, and Nocardioides, while reducing Pseudomonas, Trinickia, and Rhizomicrobium. Nitrogen deposition had a comparatively weaker effect on the functional microbial community. Correlation analysis between metabolites and functional genes suggested that alkaloids, organic acids, and phenolic compounds may be key drivers of microbial functional shifts. Overall, our findings demonstrate that warming has a greater influence than nitrogen deposition on shaping the rhizosphere soil microbial community and enhancing nutrient cycling functions, potentially increasing the risk of A. trifida invasion under future climate change.